Kajian Strukturalisme dalam Melahirkan Sebuah Karya Seni - mukhsin Patriansah (Besaung : Jurnal Seni Desain dan Budaya, 2021)
Structuralism for its adherents assumes that in humans there is a basic ability inherited genetically, so that this ability exists in all normal humans, namely the ability to structure, to structure, construct a structure, or attach a certain structure to the symptoms that it faces . The above statement assumes that every human being has the ability to create works of art from existing phenomena and is able to analyze the phenomena or phenomena with a structured method. Structural theory of language above that makes Levi-Strauss managed to see something behind the manifestation of human work. A work of art is a representation of students seeing phenomena or issues in their environment. This phenomenon makes artists feel touched and arouse and tickle their feelings to express it through the medium of art. Behind the manifestation of human work in it contains the value and meaning to be conveyed. These values and meanings have unconsciously shaped someone's ideas or thoughts. Thus it can be said that anything in this world according to Levi-Satruss's view is a system that has structures that govern it. In Structuralism the signifiant order or marker precedes meaning, in other words that talking about the existence of humans is actually not as a subject, on the contrary the existence and structure itself speaks of itself through human speech about existence.